MINAT SANTRI DALAM MENGIKUTI KEGIATAN LINGKAR SORE BAHASA ARAB DI PUSAT PENDIDIKAN ISLAM MUHARRIKUN NAJAAH: TINJAUAN PSIKOLOGI PENDIDIKAN ISLAM - Abdul Latif; Mahasri Shobahiya (Jurnal Psikotes, 2026)
Non-formal learning activities in Islamic boarding schools have an important role in improving the ability of students, including in mastering Arabic. This study aims to describe the level of interest of students in participating in the Arabic Afternoon Circle activity at the Muharrikun Najaah Islamic Education Center and analyze the factors that influence it in the perspective of Islamic educational psychology. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study showed that the interest of students was influenced by internal factors such as motivation, learning needs, and perception of lessons; as well as external factors such as the relationship between teachers and students, the learning environment, and the design of non-formal learning. These findings are relevant to the theory of learning interest and motivation in Islamic educational psychology, as well as supported by previous research emphasizing the importance of positive relationships between teachers and learners (Apriliano & Shobahiya, 2024), religious discipline in character formation (Abror & Shobahiya, 2024), as well as the dynamics of learning behavior of generation Z (Firdayanti & Shobahiya, 2024). This research emphasizes that non-formal activities such as Lingkar Sore are strategic spaces to foster students' interest in learning holistically, both from cognitive, affective, and spiritual aspects.